1997
DOI: 10.1159/000201448
|View full text |Cite
|
Sign up to set email alerts
|

Production and Activation of Hepatocyte Growth Factor during the Healing of Rat Gastric Ulcers

Abstract: The hepatocyte growth factor has been reported to be a potent mitogen of various epithelial cells, including gastric mucosal cells. Therefore, production and activation of hepatocyte growth factor in the gastric wall were investigated to speculate on the possible role of this factor in the healing of gastric ulcer in rats. Indomethacin-induced gastric mucosal lesions and acetic acid induced ulcers were employed as models of acute gastric lesions and chronic ulcer, respectively. Immunoblot and Northern blot ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

1998
1998
2009
2009

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 14 publications
1
16
0
Order By: Relevance
“…This hypothesis may agree with the fact that the cells which expressed HAI-1 protein in this study are susceptible to HGF/SF. For example, HGF/SF is an important mitogen for the gastric, bile duct, and renal tubule epithelium (Kawaida et al 1994;Takahashi et al 1995;Matsumoto and Nakamura 1996;Kinoshita et al 1997) and Schwann cells (Kranoselsky et al 1994). However, another important target of HGF/SF, hepatocytes, did not express HAI-1 protein, and bronchial and alveolar epithelia, which are also susceptible to HGF/SF (Ohmichi et al 1996), expressed a very low level of HAI-1 protein.…”
Section: Discussionmentioning
confidence: 99%
“…This hypothesis may agree with the fact that the cells which expressed HAI-1 protein in this study are susceptible to HGF/SF. For example, HGF/SF is an important mitogen for the gastric, bile duct, and renal tubule epithelium (Kawaida et al 1994;Takahashi et al 1995;Matsumoto and Nakamura 1996;Kinoshita et al 1997) and Schwann cells (Kranoselsky et al 1994). However, another important target of HGF/SF, hepatocytes, did not express HAI-1 protein, and bronchial and alveolar epithelia, which are also susceptible to HGF/SF (Ohmichi et al 1996), expressed a very low level of HAI-1 protein.…”
Section: Discussionmentioning
confidence: 99%
“…Methotrexate exerts its toxicity by directly inhibiting DNA synthesis, leading to a reduction of mitosis in the crypts and shortening of the villi (Trier, 1962;Altmann, 1974), followed by proliferative recovery phase after the damage (Taminiau et al, 1980). Previous in vivo studies have demonstrated that HGF plays an important role in gastric ulcer repair, and in vitro studies have shown that HGF stimulates intestinal cell proliferation and restitution (Kinoshita et al, 1997;Goke et al, 1998;Nishimura et al, 1998). Despite these reports, limited in vivo studies have been undertaken to investigate the role of HGF in intestinal growth and repair (Kato et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…HGF is reported to exist in various organs, liver, kidney and lung. [27][28][29] In vitro experiments revealed that, when organ injury occurs, HGF is activated and thus plays an important role in organ regeneration and tissue repair. [30][31][32][33] The activated form of HGF was also detected clinically in the ascitic fluid of patients Figure 3 The suppression of GB-d1 migration by AdCMV.NK4 infection.…”
Section: Discussionmentioning
confidence: 99%